Bacterial diversity and antibacterial activity of fermented buni fruit (Antidesma bunius) kombucha - OKTIRA ROKA AJI; TRIANIK WIDYANINGRUM; PUTRI NABELA (Society for Indonesian Biodiversity, 2025)
Abstract. Aji OR, Widyaningrum T, Nabela P. 2025. Bacterial diversity and antibacterial activity of fermented buni fruit (Antidesma bunius) kombucha. Biodiversitas 26: 3781-3790. Kombucha is a fruit-based fermented beverage with a number of health benefits. Fruit-based substrates can enhance their nutritional value and microbial diversity. This study aimed to characterise the bacterial diversity and antibacterial activity of kombucha produced from buni (Antidesma bunius) fruits. Buni kombucha was fermented statically for 7, 14, and 21 days, and bacterial diversity was analysed by 16S rRNA (V3-V4) amplicon sequencing using the SILVA database. Antibacterial activity was evaluated against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus subtilis using the agar well diffusion method. Metagenomic analysis revealed Komagataeibacter ( 80%) as the dominant genus, while low-abundance taxa such as Lactobacillus, Bacillus, and Bifidobacterium were detected; trace gut-associated genera (e.g., Bacteroides, Prevotella) likely originated from the pectin-rich substrate. Antibacterial activity increased significantly with fermentation time (p<0.05), with the strongest inhibition after 21 days: 13.83 ± 0.29?mm (S. aureus), 13.70 ± 0.61?mm (P. aeruginosa), 12.23 ± 0.25?mm (B. subtilis), and 10.77 ± 0.70?mm (E. coli). These results demonstrate that buni kombucha harbours a diverse microbiota and exhibits broad-spectrum antibacterial activity, supporting its potential as a postbiotic-rich functional beverage derived from local tropical fruits.